Political parties and generations in Paraguay's liberal era 1869 - 1940 - Lewis, Paul H. (Univ. of North Carolina Press, 1993)
From a North American perspective, the turbulence that dominated Paraguayan politics during the Liberal Era (1869-1940) appears so pervasive as to approach anarchy. But in this seemingly haphazard succession of administrations, political machines, and governmental systems, Paul Lewis sees a pattern of evolution. His pathbreaking examination of political institutionalization employs the concept of political generations to explain Paraguayan conflict and change while analyzing a significant but understudied period of Paraguayan history. Lewis chronicles the growth of the two major Paraguayan parties, the Liberals and the Colorados, from their early days as political clubs through a period of personalist caudillo politics, national machine politics, and finally institutionalized party politics. He argues that coalitions formed along generational lines to pursue goals based on shared interests and then held power until a new - and often younger - group with a different political agenda pushed them aside. By tying the rise and fall of party fortunes to generational change, Lewis constructs a multistage theory of political party development. Through this case study, he makes sense not only of Paraguay's Liberal Era but also of political turmoil in many Latin American states.
Keywords: Geschichte 1869-1940; Partidos políticos - Paraguay - Historia; Politieke partijen; Politieke situatie; Geschichte; Partei; Politik; Politische Situation; Political parties -- Paraguay -- History; Parteipolitik; Paraguay - Gobierno - 1870-1938; Paraguay - Gobierno - 1938-1954; Paraguay - Política - 1870-1938; Paraguay - Política - 1938-1954; Paraguay - Política y gobierno - 1938 1954; Paraguay -- Politics and government -- 1870-1938; Paraguay -- Politics and government -- 1938-1954; Paraguay